Efeitos da punição positiva de repetições sobre a variabilidade comportamental reforçada positivamente sob contingência Lag n - Calza, Cibele Kátia Faria (2024)
In previous research carried out with rats, the emission of sequences that did not meet the variation criterion of the Lag n contingency was punished with the presentation of an electrical stimulus, with a slight reduction in variation being observed as an effect of the punishment. However, it was not possible to discern whether this finding was due to the punishment contingency, or the nature of the punishing stimulus used, which can elicit motor responses incompatible with the variation. Considering this, this work aimed to replicate the aforementioned study with human participants, using a tone as a punisher stimulus. Fourteen participants were exposed to an ABCAB design. In Phase A, the emission of sequences that differed from the four previous sequences was reinforced with the presentation of points (Lag 4). In Phase B, the same Lag 4 contingency was employed; however, the emission of sequences that did not meet the variation criterion was followed by 1 s of black screen during which a 90 dB tone was presented (Lag 4+). In phase C, the presentation of points and tone after the emission of sequences followed the same distribution obtained in Phase B (Yoked), so that variation was allowed, but not required. As a result, in 20 of the 28 transitions from Lag 4 to Lag 4+ present in the study, positive punishment had the effect of reducing the U value in the Lag 4+ phase. However, in approximately half of these 28 transitions, an increase in the percentage of reinforcement was found due to the reduction in the frequency of sequences that did not meet the Lag 4 contingency criterion. Thirteen of the 14 participants showed a reduction in the U value during exposure to Yoked. It is suggested that the reduction in the levels of variability observed in the previous study cannot be attributed to the type of aversive stimulation used (electrical stimulus instead of sound) and that positive punishment, although it may have the effect of reducing general levels of variation, may sometimes favor or disfavor the achievement of the Lag n contingency criterion